Promoting Tourism Entrepreneurship: Entrepreneurs’ Perceptions of Tourism Development and Knowledge Management Awareness in Kathmandu Valley - Shilpakar, Anju; K.C., Anup; Lawaju, Purnima (NCC Journal, 2025)
Tourism plays a pivotal role in the economic and socio-cultural development of developing countries like Nepal, where entrepreneurs serve as key actors in shaping tourism growth, competitiveness, and sustainability. In this context, the objective of this study is to examine the perception of tourism entrepreneurs on tourism development and their awareness level of knowledge management in Kathmandu valley. Explanatory research design is used by taking 350 samples of tourism entrepreneurs in Kathmandu valley through purposive sampling methods. Social Exchange Theory is used. The study reveals that tourism entrepreneurs exhibit moderate awareness of knowledge management, with an overall index of 71.20%. Predominantly, these entrepreneurs are married male youths engaged in handicraft businesses, holding a bachelor’s degree, residing in joint families, and possessing less than five years of experience in the tourism sector. Structural analysis indicates that personal benefits from tourism development (β = 0.262, p = 0), perceived positive tourism impacts (β = 0.174, p = 0.001), perceived negative tourism impacts (β = -0.182, p = 0), and overall community satisfaction (β = 0.223, p = 0) exert significant effects on attitudes toward additional tourism development. Among the challenges identified, employees’ lack of knowledge management awareness emerges as the most prominent. Managerial interventions, particularly the implementation of knowledge management awareness programs by the organization, are recommended to mitigate these challenges and enhance the effectiveness of knowledge management practices. The findings provide insights for tourism entrepreneurs and relevant stakeholders, including the Nepal Tourism Board and local authorities, to enhance knowledge management and inform policies for tourism development.